Ramadan Fasting Exerts Immunomodulatory Effects: Insights from a Systematic Review - Adawi, Mohammad; Watad, Abdulla; Brown, Stav; Aazza, Khadija; Aazza, Hicham; Zouhir, Mohamed; Sharif, Kassem; Ghanayem, Khaled; Farah, Raymond; Mahagna, Hussein; Fiordoro, Stefano; Sukkar, Samir Giuseppe; et al. (Frontiers in Immunology, 2017)
Ramadan is the ninth month of the Islamic lunar calendar, and is observed by Muslims as a month of fasting. All Muslim adults are expected to fast, nevertheless certain subgroups are exempted including the sick, frail and pregnant women among others. Ramadan fasting have been shown to impact body systems in different manners. The influence of Ramadan fasting on immune system regulation remains elusive, however. Regulating body response to various infectious, stressful and other harmful events, immune system changes are of great interest during fasting. In this paper, we performed an extensive systematic literature review of ISI Web of Science (WoS), Scopus, MEDLINE/PubMed, Google Scholar, DOAJ, EbscoHOST, Scirus, Science Direct, the Cochrane Library and ProQuest using using the following key words: “fasting”, “Ramadan”, “Islam”, and “immunity”. Conclusions drawn from these findings included: 1- Ramadan fasting has been shown to only mildly influence the immune system and the alterations are transient and return to basal pre-Ramadan status. 2- Ramadan fasting during the second trimester of pregnancy was shown to be safe and did not result in negative fetal outcomes, or maternal oxidative status alterations.3- In cardiac patients, Ramadan fasting can have beneficial effects including lipid profile improvement and alleviation of oxidative stress. 4-In asthmatic patients as well as in patients with HIV/AIDS and autoimmune disorders, fasting was safe. 5-In psychiatric patients, such as those suffering from schizophrenia, fasting could increase immunologic markers. 6- Fasting Muslim athletes who maintain intensive training schedule during Ramadan show fluctuations of immune markers.